SCOPE AND ETHICAL CONSIDERATIONS OF AI IN JOURNALISM: THE PERSPECTIVE OF JOURNALISM STUDENTS - Nedeljković, Marko; Krstić, Aleksandra (Serbian political thought, 2025)
This study examines the perceptions of journalism students at the University of Belgrade concerning the integration of artificial intelligence (AI) into the journalistic profession. Specifically, it explores their opinions toward the potential benefits and drawbacks of AI, its appropriate and inappropriate applications in newsroom settings, and the ethical dilemmas it may pose. The research was conducted among 204 final-year journalism students from the Faculty of Political Sciences at the University of Belgrade. A mixed-method survey was used, incorporating both closed and open-ended questions, as well as rating scales, to gather comprehensive data. Findings suggest that future media professionals are highly aware of the growing influence of AI on journalism. A significant majority of respondents perceive AI as having a strong or very strong impact on the field, while only a small number consider its influence to be minimal or limited. Although participants acknowledge both the opportunities and challenges posed by AI, the overall perception of its impact on journalism is predominantly negative.